Wave overtopping and splash-up at seawalls with bullnose - Trung, Le Hai; Linh, Dang Thi; Tho, Tang Xuan; Duy, Nguyen Truong; Tung, Tran Thanh (Vietnam Journal of Marine Science and Technology, 2020)
Seawalls have been erected to protect hundreds of towns and tourism areas stretching along the coast of Vietnam. During storm surges or high tides, wave overtopping and splash-up would often threaten the safety of infrastructures, traffic and residents on the narrow land behind. Therefore, this study investigates these wave-wall interactions via hydraulic small scale model tests at Thuyloi University. Remarkably, the structure models were shaped to have different seaward faces and bullnoses. The wave overtopping discharge and splash run-up height at seawalls with bullnose are significantly smaller than those without bullnose. Furthermore, the magnitude of these decreasing effects is quantitatively estimated.